Factors That Postpartum Interest In Vitamin A Consumption In The Helvetia Medan Health Center Area In 2021 - Riska Maulidanita; Zakiyah (Institute of Computer Science (IOCS), 2022)
The KVA (Vitamin A Deficiency) management program that has been implemented is to supplementation of high doses of vitamin A capsules 2 times per year in Toddlers and Mothers of Nifas. The purpose of this study is to find out the factors that affect the interest of postpartum mothers towards vitamin A consumption in the Helvetia Medan Health Center Region in 2021. The design of this research uses analytical survey design, with a cross sectional approach. The sample in the study used a total population of 52 respondents. Data collection techniques use questionnaires and data analysis in the form of univariate, bivariate and multivariate analysis. The results of the chi square statistical test study obtained a p-value age of 0.022, knowledge of 0.03, distance to health services p-value 0.023, husband support p-value 0.04 and health worker support 0.002. Based on multivariate results known exp(B)/OR value at the age of 9,078, knowledge 1,181, distance to access to health services 33,229, husband support 7,035 and health worker support 4,353. The study concludes that there is a relationship between the influence of age, knowledge, husband support and health care support.